2017
DOI: 10.1007/s10072-017-3046-y
|View full text |Cite
|
Sign up to set email alerts
|

A high-urgency stroke code reduces in-hospital delays in acute ischemic stroke: a single-centre experience

Abstract: Timely treatment is essential in acute ischemic stroke as the chances of recovery diminish over time, so efforts are necessary to streamline in-hospital pathways and reduce delays. Here, we analyse the interventions to reduce door-to-needle time in stroke patients suitable for intravenous thrombolysis at the Emergency Department of San Carlo Borromeo Hospital, Milan, Italy. All stroke patients consecutively treated with intravenous thrombolysis at our centre from January 1, 2013 to December 31, 2015 were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In a study by Ruff et al a formal case-based clinical “boot camp” for incoming junior neurology residents resulted in 25 min DNT reduction in patients managed by junior staff ( 20 ). Other centers have also incorporated regular feedback and education sessions as an ongoing feature of the stroke pathway ( 5 , 14 , 21 ). Our emphasis to the rotating residents is to contact the on-call neurologist early for all cases particularly in cases with diagnostic uncertainty adopting the “if in doubt, call out” mantra.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Ruff et al a formal case-based clinical “boot camp” for incoming junior neurology residents resulted in 25 min DNT reduction in patients managed by junior staff ( 20 ). Other centers have also incorporated regular feedback and education sessions as an ongoing feature of the stroke pathway ( 5 , 14 , 21 ). Our emphasis to the rotating residents is to contact the on-call neurologist early for all cases particularly in cases with diagnostic uncertainty adopting the “if in doubt, call out” mantra.…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of tPA diminishes with treatment delay ( 1 , 2 ); every minute delay to treatment is associated with nearly two disability free health days lost ( 2 ). Successful reduction in stroke treatment times through implementing systematic thrombolysis protocol has been reported in stroke centers around the world ( 3 5 ) with the most rapid stroke treatment reported to-date achieved in Helsinki ( 6 ). The Helsinki stroke model consisted of 12 interventions aimed at reducing treatment delays prior to thrombolysis and the adaptation of this model resulted in 18-min reduction in thrombolysis delay to 25 min in Melbourne within 4 months ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…There were studies conducted by centers to analyze DTN time by introducing a stroke nurse, response unit or designed code [ 11 , 14 16 ]. Previous studies showed that good intervention could limit delays and improve DTN time [ 11 , 16 19 ]. In our study, we found that from 2016 to 2020 the median DTN time significantly decreased from 36 to 25 min.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors reported that multidisciplinary streamlining (continuous feedback, standardised immediate emergency department attendance, interventional team activation for all potential interventions, pre-notification by the EMS, minimising additional diagnostic testing and direct transport to the CT scanner and then to the angiography suite) resulted in a significantly shorter duration to recanalisation [40]. Many other reports strongly suggest that multidisciplinary streamlining of care in stroke patients results in faster reperfusion and better outcomes [41,42].…”
Section: From Stroke Managementmentioning
confidence: 99%